A method for preparing an anti-corrosion coating on a non-valve metal surface
By cold spraying the aluminum layer on the non-valve metal surface and plasma electrolytic oxidation, combined with the method of growing Zn-Al-LDHs in situ, the problem of difficulty in forming an anticorrosion coating on the non-valve metal surface is solved, and efficient anticorrosion protection is achieved, and the process is safe, green and simple.
Patent Information
- Application Number
- CN202211630995.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-12-19
AI Technical Summary
The prior art is difficult to effectively form an anticorrosion coating on the non-valve metal surface, and after plasma electrolytic oxidation, it faces problems such as reduced service performance after heating of the matrix, poor film density, uneven film thickness, and corrosion media are prone to enter the holes in the film layer at weak places, causing corrosion.
By cold spraying the aluminum layer on the non-valve metal surface, plasma electrolytic oxidation is performed to form an alumina ceramic film, and finally Zn-Al-LDHs are grown in situ, and the porous layer of the plasma electrolytic oxide film is closed to achieve protection against the non-valve metal surface.
It significantly improves the anti-corrosion effect of the non-valve metal surface, avoids the poor density of the film layer and the uneven film thickness after plasma electrolysis oxidation, and enhances the barrier ability to corrosive media, and the process is green, safe and simple.
Smart Images

Figure CN116005224B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface protection treatment, and in particular relates to a method for preparing a non-valve metal surface anti-corrosion coating. Background Art
[0002] Plasma electrolytic oxidation is an advanced surface treatment technology developed from traditional anodizing, which is used to form ceramic coatings on valve metals (aluminum, magnesium, titanium and zirconium, etc.) and their alloys. The technology works at high voltage, resulting in dielectric breakdown of the oxide film on the metal surface, characterized by mobile plasma discharge at the metal / electrolyte interface. For non-valve metals such as carbon steel, iron, copper and nickel, plasma electrolytic oxidation is generally considered impractical because it is impossible to produce a stable spark state that is essential for the growth of plasma electrolytic oxidation coatings. Usually for non-valve metals, here taking steel as an example, one method is to directly plasma electrolytically oxidize the metal by controlling the experimental conditions, but this method has extremely harsh requirements on the experimental conditions and is still in the experimental exploration stage; another method is to perform secondary treatment on the surface of the metal material, such as hot-dip aluminum plating and then oxidation. This process method is too cumbersome and the process itself requires the metal to be heated to a molten state. The alloy coating is prone to oxidation phase change and the workpiece itself is also prone to failure due to the generation of large thermal stress. Summary of the invention
[0003] In order to solve the above-mentioned problems in the prior art and form an effective protective layer on the surface of non-valve metal, the present invention provides a method for preparing an anti-corrosion coating on the surface of non-valve metal, by first cold spraying an aluminum layer on the surface of the non-valve metal, then performing plasma electrolytic oxidation, preparing an alumina ceramic film on the surface of the non-valve metal, and finally in-situ generating LDHs that can effectively seal the porous layer of the plasma electrolytic oxidation film itself, thereby achieving a fundamental improvement in the protective performance of the non-valve metal surface. This process preparation scheme is green, safe and simple.
[0004] In order to achieve the purpose of the present invention, the technical solution adopted is as follows:
[0005] A method for preparing an anti-corrosion coating on a non-valve metal surface comprises the following steps:
[0006] (1) The surface of the non-valve metal workpiece is sequentially sandblasted and cold sprayed to form an Al coating;
[0007] (2) Plasma electrolytic oxidation is performed on the surface of the Al coating formed by cold spraying to form an aluminum oxide film;
[0008] (3) In-situ growth of Zn-Al-LDHs film: The non-valve metal workpiece after plasma electrolytic oxidation is encapsulated and then placed in a mixed solution of zinc nitrate hexahydrate and ammonium nitrate for in-situ growth. The reaction temperature is 90°C to 100°C and the reaction time is 15 to 30 hours. Finally, an Al2O3 / Zn-Al-LDHs composite coating is obtained to achieve corrosion protection of non-valve metals.
[0009] (4) The workpiece after the reaction is ultrasonically cleaned, then rinsed with deionized water, and placed in a drying oven for drying.
[0010] Furthermore, the process parameters of cold spraying are as follows: both the powder feeding gas and the working gas are compressed air, the gas pressure is 0.8-1.2 MPa, the gas heating temperature is 400°C-600°C, the powder feeding amount is 40-60 g / min, the distance between the spray gun and the substrate surface during cold spraying is 10-12 mm, and the relative movement speed between the spray gun and the substrate is 10-12 mm / s.
[0011] Furthermore, the thickness of the Al coating formed by cold spraying is 200 μm to 500 μm.
[0012] Furthermore, epoxy resin and curing agent are used to seal the non-processed area of the non-valve metal workpiece before plasma electrolytic oxidation, exposing only the cold sprayed surface, and the bottom of the substrate is connected with a copper wire. The ratio of epoxy resin to curing agent is 1:1. The present invention can selectively prepare Al2O3 / Zn-Al-LDHs composite coatings on specific surfaces of non-valve metal workpieces, and can also prepare composite coatings on all exposed surfaces of the workpiece.
[0013] Furthermore, the bath solution used for plasma electrolytic oxidation contains 12 g / L sodium silicate nonahydrate, 5 g / L potassium hydroxide, and 0.5 g / L sodium fluoride.
[0014] Furthermore, the specific parameters of the plasma electrolytic oxidation method are: the non-valve metal workpiece is used as the anode, the stainless steel tank is used as the cathode, the power supply is a pulsed AC power supply, the constant current mode is used, and the current density is 20-50A·dm -2 ,The oxidation time is 20 min, the frequency is 600 Hz, the duty ratio is 20%, and the electrolyte temperature is controlled below 30 ℃ by the water cooling system.
[0015] Furthermore, before the in-situ generation of LDHs, the plasma electrolytically oxidized sample was taken out and resealed with epoxy resin and curing agent, exposing only the plasma electrolytically oxidized surface. The ratio of epoxy resin to curing agent was 1:1.
[0016] Furthermore, calculated by mass concentration, the mixed solution contains 1.0-2.0 mg / mL zinc nitrate hexahydrate and 20-30 mg / mL ammonium nitrate.
[0017] Furthermore, ammonia water is added dropwise to adjust the pH value of the mixed solution of zinc nitrate hexahydrate and ammonium nitrate to neutral.
[0018] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0019] In the conventional technology, it is difficult for the non-valve metal surface to be subjected to plasma electrolytic oxidation, and the service performance after the substrate heating faced by plasma electrolytic oxidation is reduced, the film layer density is poor, the film thickness is uneven, the corrosive medium easily enters from the holes of the weak film layer to cause corrosion, and the production process is complicated. However, the present invention provides conditions for plasma electrolytic oxidation by first cold spraying an aluminum layer on the surface of a non-valve metal workpiece, and then forms a plasma electrolytic oxidation film (alumina ceramic film) on the non-valve metal, and finally overcomes the defects of the plasma electrolytic oxidation film by in-situ growth of Zn-Al-LDHs, and the porous layer of the plasma electrolytic oxidation film itself is effectively closed, specifically, Zn-Al-LDHs is in-situ growth on an alumina ceramic film with sufficient binding force, and the corrosion inhibition characteristics and super-hydrophobic characteristics of Zn-Al-LDHs themselves prevent the corrosive medium from entering from the thinner part of the plasma electrolytic oxidation film, greatly improving the anti-corrosion effect on the surface of the non-valve metal. The preparation scheme of this process is green, safe, and simple in process.
[0020] 2. The present invention realizes the preparation of selective Al2O3 / Zn-Al-LDHs composite coating on specific surfaces of the workpiece by sealing the workpiece at specific steps. The composite coating can also be prepared on all exposed surfaces of the workpiece. It is finally found that the coating is not affected by the sealing step whether in the preparation stage of the Al2O3 film or the in-situ generation stage of the Zn-Al-LDHs. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings described herein are used to further explain the present invention and constitute a part of this application. The schematic diagrams of the present invention are used to explain the present invention and do not constitute an improper limitation of the present invention. The protection scope of the present invention is not limited to the following schematic diagrams.
[0022] Figure 1 This is the surface micromorphology of different areas of the sample obtained in Example 1.
[0023] Figure 2 This is the surface micromorphology of the sample obtained in Example 1 after plasma electrolytic oxidation.
[0024] Figure 3 This is the surface micromorphology of the Al2O3 / Zn-Al-LDHs composite film obtained in Example 1.
[0025] Figure 4This is the surface micromorphology of the sample obtained in Example 2 after plasma electrolytic oxidation.
[0026] Figure 5 These are the three-dimensional contour diagram and three-dimensional contour related data of the sample obtained in Example 2 after plasma electrolytic oxidation.
[0027] Figure 6 This is the surface micromorphology of the Al2O3 / Zn-Al-LDHs composite film obtained in Example 2.
[0028] Figure 7 It is the temperature of the substrate surface when the workpiece is processed by four technologies: cold spraying, hot-dip aluminum plating, PVD, and CVD.
[0029] Figure 8 It is a comparison diagram of polarization curves of the samples obtained from Comparative Example 1 and Comparative Example 2, Example 1 and Example 2 in 3.5% NaCl electrolyte. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with embodiments:
[0031] Comparative Example 1:
[0032] First, the q345 steel sample was ultrasonically cleaned and degreased in an acetone solution, then pickled and alkali washed (the pickling liquid was diluted hydrochloric acid, the alkali washing liquid was 0.015g / L sodium hydroxide, and the pickling and alkali washing were 5 minutes each). After the workpiece surface was rinsed with clean water, the sample was plated with a plating agent. The plating agent liquid composition was 0.015g / L sodium chloride, 0.015g / L potassium chloride, 0.01g / L sodium fluoride, and 0.01g / L potassium fluoride. A medium-frequency induction furnace was used to heat the pure aluminum ingot (99.9%) to a molten state at a heating temperature of 700°C. The sample was hot-dip aluminum-plated for 60s. After aluminum plating, the sample was water-cooled. After completion, the sample surface was polished. The sample surface was subjected to plasma electrolytic oxidation. The plasma electrolytic oxidation bath liquid composition was 12g / L sodium silicate nine hydrate, 5g / L potassium hydroxide, and 0.5g / L sodium fluoride. Q345 steel was used as the anode, stainless steel tank was used as the cathode, pulse AC power was used as the power source, constant current mode was used, and the current density was 40A·dm -2 ,The oxidation time is 20 min, the frequency is 600 Hz, the duty ratio is 20%, and the electrolyte temperature is controlled below 30 ℃ by the water cooling system.
[0033] Figure 1 This is the surface microscopic morphology of the sample obtained in Example 1. It can be seen that large holes appear in many places on the surface of the sample.
[0034] Embodiment 1:
[0035] The surface of the q345 steel sample was sandblasted and then cold sprayed to form an Al coating. The original powder material used for cold spraying was: Al metal powder with a powder particle size of 20-30 μm and a purity of 99.9%. Compressed air was used as the gas for cold spraying, and the powder feeding amount was set to 40-60 g / min, the gas pressure was 0.99 MPa, and the gas heating temperature was 600 ° C (at 400 ° C, 500 ° C and 600 ° C, a good cold spraying effect can be obtained to meet the further in-situ growth requirements, and the deposition effect is best at 600 ° C). The distance between the cold spraying and the substrate surface was set to 10 mm, the relative movement speed between the spray gun and the substrate was 10 mm / s, and the coating thickness was 200 μm. The sample surface was subjected to plasma electrolytic oxidation, and the composition of the plasma electrolytic oxidation tank liquid was 12 g / L of sodium silicate nine hydrate, 5 g / L of potassium hydroxide, and 0.5 g / L of sodium fluoride. Q345 steel was used as the anode, stainless steel tank was used as the cathode, pulse AC power was used as the power source, constant current mode was used, and the current density was 20A·dm -2 , the oxidation time is 20min, the frequency is 600Hz, the duty cycle is 20%, and the electrolyte temperature is controlled below 30℃ by the water cooling system. The sample subjected to plasma electrolytic oxidation in the current step is placed in a high-pressure reactor. The solution is calculated by mass concentration. The concentration of zinc nitrate hexahydrate in the mixed solution is 0.7mg / mL and the concentration of ammonium nitrate is 25mg / mL. Distilled water is used to dissolve the drugs. The mixed solution is ultrasonicated for 30min and ammonia water is added to make the pH of the solution neutral. Then the mixed solution is poured into the reactor, the reactor is tightened, and it is placed in a blast drying oven for in-situ growth. The temperature of the blast drying oven is set to 100℃, and the constant temperature time is set to 30h.
[0036] Figure 2 This is the surface microscopic morphology of the sample obtained in Example 1 after plasma electrolytic oxidation. It can be seen that the plasma electrolytic oxidation film prepared under this current density has a slightly higher porosity, larger pores, an uneven "crater" morphology, and a relatively large roughness.
[0037] Figure 3 The surface microstructure of the Al2O3 / Zn-Al-LDHs composite film obtained in Example 1 shows that the in-situ grown Zn-Al-LDHs did not completely cover the pores of the plasma electrolytic oxidation film.
[0038] Example 2
[0039] The surface of the Q345 steel sample is sandblasted and then cold sprayed to form an Al coating. The original powder material selected in this embodiment is: Al metal powder with a powder particle size of 20 to 30 μm and a purity of 99.9%. Compressed air is used as the gas for cold spraying, and the powder feeding amount is set to 40 to 60 g / min, the gas pressure is 0.99 MPa, and the gas heating temperature is 600°C. The distance between the cold spraying and the substrate surface is set to 10 mm, the relative movement speed between the spray gun and the substrate is 10 mm / s, and the coating thickness is 200 μm. The sample surface is subjected to plasma electrolytic oxidation, and the plasma electrolytic oxidation tank liquid composition is 12 g / L of sodium silicate nonahydrate, 5 g / L of potassium hydroxide, and 0.5 g / L of sodium fluoride. Q345 steel is used as the anode, the stainless steel tank is used as the cathode, the power supply is a pulsed AC power supply, and the constant current mode is adopted. The current density is 40 A·dm -2 , the oxidation time is 20min, the frequency is 600Hz, the duty cycle is 20%, and the electrolyte temperature is controlled below 30℃ by the water cooling system. The sample subjected to plasma electrolytic oxidation in the current step is placed in a high-pressure reactor. The solution is calculated by mass concentration. The concentration of zinc nitrate hexahydrate in the mixed solution is 0.7mg / mL and the concentration of ammonium nitrate is 25mg / mL. Distilled water is used to dissolve the drugs. The mixed solution is ultrasonicated for 30min and ammonia water is added to make the pH of the solution neutral. Then the mixed solution is poured into the reactor, the reactor is tightened, and the reactor is placed in a blast drying oven for in-situ growth to obtain an Al2O3 / Zn-Al-LDHs composite membrane with corrosion protection. The temperature of the blast drying oven is set to 100℃, and the constant temperature time is set to 30h.
[0040] Figure 6 This is the surface microstructure of the Al2O3 / Zn-Al-LDHs composite film obtained in Example 2. From the figure, it can be seen that the plasma electrolytic oxidation film is covered by the in-situ generated LDHs, and almost no Figure 3 The holes on the surface, Zn-Al-LDHs completely fill the holes of the plasma electrolytic oxide film, and seal the holes. The microscopic morphology of the in-situ generated Zn-Al-LDHs can be seen more clearly. Zn-Al-LDHs has two microscopic morphologies, one is a typical lamellar structure, densely growing around and on the holes, and the other is a cylindrical structure, scattered around the lamellar structure.
[0041] The samples obtained from Comparative Example 1, Comparative Example 2, Example 1 and Example 2 were subjected to corrosion resistance tests, and the testing instrument was a Princeton P4000 electrochemical workstation. Figure 8 It is a comparison diagram of polarization curves of samples obtained from Example 1, Example 2, Example 1 and Example 2 in 3.5% NaCl electrolyte. Table 1 is the corrosion voltage and corrosion current density of samples obtained from Example 1, Example 2, Example 1 and Example 2. Figure 8 From Table 1, it can be concluded that the corrosion voltage of plasma electrolytic oxidation after hot-dip aluminum plating on the non-valve metal surface of Comparative Example 1 is -1093mV, and the corrosion voltage of plasma electrolytic oxidation after cold spraying on the non-valve metal surface of Comparative Example 2 is -910.299mV, which shows that the corrosion resistance of Comparative Example 2 is stronger than that of Comparative Example 1. This is mainly because larger holes appear in the film layer after hot-dip plating (no leak plating). The corrosion voltage of the Al2O3 / Zn-Al-LDHs composite film prepared after cold spraying on the non-valve metal surface of Example 2 is -725.363mV, and the corrosion voltage of the sample in Example 2 is the highest. The corrosion current density of the sample in Example 2 is smaller than that of Comparative Example 1, Comparative Example 2, and Example 1, and the corrosion current density of the sample in Example 2 is reduced by 1 order of magnitude compared with the corrosion current density of Comparative Example 1. From Figure 8 From Table 1, it can be concluded that the sample in Example 2 has the best corrosion resistance.
[0042] It should be noted that the lower the surface roughness and the smaller the porosity, the higher the anti-corrosion performance of the protective film obtained after in-situ growth.
[0043] Table 1 Corrosion voltage and corrosion current density of samples obtained in Comparative Example 1, Comparative Example 2, Example 1 and Example 2
[0044]
[0045] Comparative Example 2:
[0046] The surface of the Q345 steel sample is sandblasted and then cold sprayed to form an Al coating. The original powder material selected in this embodiment is: Al metal powder with a powder particle size of 20 to 30 μm and a purity of 99.9%. Compressed air is used as the gas for cold spraying, and the powder feeding amount is set to 40 to 60 g / min, the gas pressure is 0.99 MPa, and the gas heating temperature is 600°C. The distance between the cold spraying and the substrate surface is set to 10 mm, the relative movement speed between the spray gun and the substrate is 10 mm / s, and the coating thickness is 200 μm. The sample surface is subjected to plasma electrolytic oxidation, and the plasma electrolytic oxidation tank liquid composition is 12 g / L of sodium silicate nonahydrate, 5 g / L of potassium hydroxide, and 0.5 g / L of sodium fluoride. Q345 steel is used as the anode, the stainless steel tank is used as the cathode, the power supply is a pulsed AC power supply, and the constant current mode is adopted. The current density is 40 A·dm -2 ,The oxidation time is 20 min, the frequency is 600 Hz, the duty ratio is 20%, and the electrolyte temperature is controlled below 30 ℃ by the water cooling system.
[0047] Figure 4This is the surface microscopic morphology of the sample obtained in Example 2 after plasma electrolytic oxidation. It can be seen that the surface of the plasma electrolytic oxidation film prepared under this current density is smoother than that of the film in Example 1, the surface roughness is reduced, the number of holes is reduced and the size is reduced, and the film porosity is slightly reduced. However, the surface is still very rough, uneven, with large ups and downs, and the film thickness is uneven.
[0048] After a large number of experiments, the inventors found that the invention prepares an alumina ceramic film on the surface of non-valve metals and their alloys by first cold spraying on the surface of the substrate and then plasma electrolytic oxidation, and in-situ generates LDHs that can effectively seal the porous layer of the plasma electrolytic oxidation film itself. Because the in-situ generated LDHs have a strong enough binding force, the Al2O3 / Zn-Al-LDHs composite film layer is finally successfully prepared. This method not only realizes plasma electrolytic oxidation on the surface of non-valve metals, but also avoids the problem of reduced service performance after substrate heating faced by plasma electrolytic oxidation on the surface of non-valve metals. In addition, because LDHs with corrosion resistance and surface super-hydrophobicity are generated in situ on the surface of the loose and porous Al2O3 film, Zn-Al-LDHs can effectively seal the porous layer of the plasma electrolytic oxidation film itself, greatly improving the thickness and density of the coating, solving the problems of poor density of the film layer, uneven film thickness, and easy entry of corrosive media from the holes in the film layer at weak points after plasma electrolytic oxidation on the existing cold spray surface to cause corrosion, thereby achieving a fundamental improvement in the protective performance of the non-valve metal surface. The comparison results of the corrosion resistance of Al2O3 films and Al2O3 / Zn-Al-LDHs composite films prepared by different technologies show that the corrosion resistance of the sample in Example 2 is the best, which confirms that the corrosion resistance of the Al2O3 film prepared by cold spraying on the non-valve metal surface is better than that of the Al2O3 film prepared by hot dip plating on the non-valve metal surface, and Zn-Al-LDHs effectively improves the corrosion resistance of the Al2O3 film. In addition, the inventors have achieved the preparation of selective Al2O3 / Zn-Al-LDHs composite coatings on specific surfaces of the workpiece by sealing the workpiece during specific steps, and can also prepare composite coatings on all exposed surfaces of the workpiece. It was finally found that the coating was not affected by the sealing step whether in the preparation stage of the Al2O3 film or the in-situ generation stage of Zn-Al-LDHs. The preparation scheme of this process is green, safe, and simple.
[0049] The above is only a preferred specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field within the technical scope disclosed by the present invention, according to the technical solution and its concept of the present invention, shall be covered within the protection scope of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing an anti-corrosion coating on a non-valve metal surface, characterized in that: The steps include: (1) The surface of the non-valve metal workpiece is sandblasted and cold sprayed in sequence to form an Al coating; (2) Plasma electrolytic oxidation is performed on the surface of the Al coating formed by cold spraying to form an aluminum oxide film; (3) In-situ growth of Zn-Al-LDHs film: The non-valve metal workpiece after plasma electrolytic oxidation is encapsulated and then placed in a neutral mixed solution of zinc nitrate hexahydrate and ammonium nitrate for in-situ growth. The reaction temperature is 90°C to 100°C and the reaction time is 15 to 30 hours. Finally, Al2O3 / Zn-Al-LDHs composite coating is obtained; (4) After the reaction, the workpiece is ultrasonically cleaned, then cleaned with deionized water, and placed in a drying oven for drying; The non-valve metal workpiece is used as the anode, the stainless steel tank is used as the cathode, the power supply is a pulse AC power supply, the constant current mode is adopted, and the current density is 20-50A·dm -2 , the oxidation time is 20min, the frequency is 600Hz, the duty cycle is 20%, and the electrolyte temperature is controlled below 30℃ through the water cooling system; The bath solution used for plasma electrolytic oxidation contains 12 g / L sodium silicate nonahydrate, 5 g / L potassium hydroxide, and 0.5 g / L sodium fluoride.
2. The method for preparing the anticorrosion coating on the surface of non-valve metal according to claim 1, characterized in that: The process parameters of cold spraying are as follows: both powder feeding gas and working gas are compressed air, gas pressure is 0.8~1.2MPa, gas heating temperature is 400℃~600℃, powder feeding amount is 40~60g / min, the distance between the spray gun and the substrate surface during cold spraying is 10~12mm, and the relative movement speed between the spray gun and the substrate is 10~12mm / s.
3. The method for preparing the anticorrosion coating on the surface of non-valve metal according to claim 1, characterized in that: The thickness of the Al coating formed by cold spraying is 200μm~500μm.
4. The method for preparing the anticorrosion coating on the surface of non-valve metal according to claim 1, characterized in that: Calculated by mass concentration, the mixed solution contains 1.0-2.0 mg / mL zinc nitrate hexahydrate and 20-30 mg / mL ammonium nitrate.